Homicides and its relationship with permits for carrying and ownership firearms in Guatemalan municipalities (2018) - Fuentes, Cesar M. (International journal of comparative and applied criminal justice, 2023)
Guatemala has one of the highest firearm homicide rates and gun ownership per capita in the world. This paper discusses the extent to which it stands as a case to add to the routine activity hypothesis versus the fear hypothesis. Using a negative binomial regression model, this study tested the relationship between firearm possession and homicide rates in its municipalities in 2018. A new dataset at the municipal level on firearm possession and ownership for 2018 was obtained from DIGECAM. The data were obtained from the National Civil Police and the 2018 Population and Housing Census. The authors found empirical evidence stating that the absence of security, justice institutions, and regional subculture of violence leads the population to use firearms due to fear or perceived risk of self-protection.